The nest architecture of Diadasia hirta (Jörgensen) (Apidae: Emphorini) from la Rioja Province, Northwestern Argentina - Sarzetti, Laura Cristina (2011)
Nests of Diadasia hirta are documented here for the first time. Nests have a cylindrical turret, one vertical principal burrow, cells disposed in linear series, and an oval pollen mass. Almost all observed behavioral traits and nest architecture features resemble those of other species of Diadasia. One exceptional behavior observed was pollen removal from the nest.